Large deformation dynamic analysis elastoplastic solids by the finite element method I. total lagrangian formulation. - Hien, Tran Duong (Vietnam Journal of Mechanics, 1987)
An effective finite element formulation based upon the total Lagrangian desert potion is presen ted for nonlinear dynamic problems in deformable solids. Continuum is considered with large displacement, large strain and material elastoplasticity. A modified form of the Wilson ᶿ method for time integral ion of the increment equations of motion is proposed. This formulation is implementer and the results of some sample ana1yses are given.